Tipe Ruang Kreatif di Bandung dan Konteks Pendukungnya - Ihsan Maulanar Robbany; Josephin Maria Pastika Atidipta; Shabrina Amalia Ihsanti; Vadya Dzauqiah; Agus Suharjono Ekomadyo (EMARA: Indonesian Journal of Architecture, 2019)
The creative class is a group of people who utilize their creative thinking as a way to solve problems by creating innovations. The development of the creative class in the urban regions of the world results in a term called the creative city. Inside a creative city, the activity of the creative class establishes the needs for spaces that can accommodate their activities. Bandung, one of a creative city in Indonesia, has a lot of creative spaces. This research aims to map the types of creative spaces in Bandung, including their relationship with their contexts. This is achieved through the study of three cases, Kompleks Gudang Selatan, Lo.Ka.Si Coffee & Spaces, and Bandung Creative Hub. The mapping of creative spaces is done using the quantitative and qualitative scoring systems through observation, user interviews, and management interviews. Study about contexts is done using interviews and literature studies. The result of this research shows that those 3 cases, as creative spaces, are dominated by presentation space. This is supported by factors in their firm aspects. Moreover, it is found that the creative industry in Bandung is currently still oriented at presentation activities